Tuneable fluorescence enhancement over nanostructured ZnO arrays with controlled morphology - Wang,T; Centeno,A; Darvill,D; Pang,J; Ryan,MP; Xie,F (Physical Chemistry Chemical Physics, 2018)
Zinc oxide (ZnO) nanorods (NRs) have been demonstrated as a promising platform for enhanced fluorescence-based sensing. It is, however, desirable to achieve a tuneable fluorescence enhancement with these platforms so that the fluorescence output can be adjusted based on the real need. Here we show that the fluorescence enhancement can be tuned by changing the diameter of the ZnO nanorods, simply controlled by potassium chloride (KCl) concentration during synthesis, using arrays of previously developed aligned NRs (a.k.a. aligned NR forests) and nanoflowers (NFs). Combining the experimental results obtained from ZnO nanostructures with controlled morphology and computer-aided verification, we show that the fluorescence enhancement factor increases when ZnO NRs become thicker. The fluorescence enhancement factor of NF arrays is shown to have a much stronger dependency on the rod diameter than that of aligned NR arrays. We prove that the morphology of nanostructures, which can be controlled, can be an important factor for fluorescence enhancement. Our (i) effort towards understanding the structure–property relationships of ZnO nanostructured arrays and (ii) demonstration on tuneable fluorescence enhancement by nanostructure engineering can provide some guidance towards the rational design of future fluorescence amplification platforms potentially for bio-sensing.